Internet of Things Based Air Quality Monitoring System with Automatic Notification - Azizah, Devi Nur; Heranurweni, Sri; Idris, La Ode Muhamad (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2025)
Internet of Things (IoT)-based air quality monitoring systems represent a significant advancement in urban environmental management. This research implements a system that integrates PM2.5, PM10, CO2, and NO2 sensors for real-time monitoring of pollutants. The results showed that the integration of IoT technology with cloud computing and machine learning algorithms successfully created a responsive and accurate monitoring system. The model achieved maximum accuracy during the training process, with promising predictive capabilities in real-world implementation. The main findings of the study confirmed that the Weighted Class (WC) approach significantly improved performance in the testing and prediction process by addressing class imbalance in the dataset, while the Data Augmentation (DA) technique did not show the expected improvement due to the intrinsic characteristics of air quality data. The automatic notification system successfully provides early warnings when air quality exceeds specified thresholds, enabling proactive responses from authorities and the public. The implementation of a web-based monitoring dashboard provides comprehensive visualization of data for long-term analysis. This research contributes to the development of smart cities by providing an effective framework for air quality management, supporting data-driven decision-making, and increasing public awareness of environmental conditions.